Aplikasi Pembelajaran IPA Tentang Fauna Model Game untuk Sekolah Dasar dengan Metode Computer Assisted Instruction (CAI) - Manik, Edli Rumiar; Limbong, Tonni (MEANS (Media Informasi Analisa dan Sistem), 2019)
Learning in an educational institution is considered as the initial stage of the formation of identity or the basic process of education, especially in primary schools. At this time students experience educational and learning process activities should be very fun in practicing the catchment of students. For this reason, it is necessary to make a media for introducing fauna recognition game models that are available in science subjects in grade 3 elementary school. This game is a learning game with fauna introduction, fauna needs and fauna grouping. The computer is one of the tools and is a technology product that is considered to have the ability to produce learning products that are integrated with CAI (Computer Assisted Instruction), CAI has many types for the learning process including drill and practice, simulation, tutorials, and games that have been developed. In this study, learning applications were made that apply one of the CAI (Computer Assisted Instruction) methods in the form of games to increase students' interest in learning. With the help of adobe flash professional CS6 software, the application in this study was created. It is hoped that the application of the learning model of natural science games with the CAI (Computer Assisted Instruction) method can help the learning process and understanding of the material.